Gender oppression in armed conflict: feminist approach to Eider Rodriguez’s narrative - Esparza Martin, Iratxe (EGAN, 2021)
Based on the tools offered by feminist reading, we will focus on concepts such as gender, social agreements and heteronormativity, embodiment and ro- mantic love, that is, how they are reflected in the texts and how they affect in the gender position. The armed conflict is a solid base of Rodriguezs narratives, and the women protagonists are represented behind the conflict, in the shadow. Thus, we consider essential to analyse their situation, as well as the behaviour of women in the face of social, cultural and ideological norms in fiction works.